2017
DOI: 10.1016/j.alcohol.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of the nucleus accumbens identifies DNA methylation signals differentiating low/binge from heavy alcohol drinking

Abstract: Alcohol use disorders encompass a range of drinking levels and behaviors, including low, binge and heavy drinking. In this regard, investigating the neural state of individuals who chronically self-administer lower doses of alcohol may provide insight into mechanisms that prevent the escalation of alcohol use. DNA methylation is one of the epigenetic mechanisms that stabilizes adaptations in gene expression and has been associated with alcohol use. Thus, we investigated DNA methylation, gene expression and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 71 publications
(101 reference statements)
4
36
0
Order By: Relevance
“…Using this approach the rhesus monoamine oxidase A (MAO-A) expression in the blood of alcohol-naïve subjects was found to be negatively correlated with subsequent alcohol self-administration (Cervera-Juanes et al, 2015). Further, the methylation of the promoter region of the MAO-A gene was associated with MAO-A expression in blood and in the nucleus accumbens (Cervera-Juanes et al, 2016). Because MAO-A is involved in monoaminergic metabolism (serotonin, dopamine and norepinephrine), discrete epigenetic changes altering the expression of this enzyme has direct implications for homeostatic physiological and behavioral processes involved in the risk for heavy drinking.…”
Section: Ii: Assessment Of Risks For Heavy Drinking and Stress Interamentioning
confidence: 99%
See 2 more Smart Citations
“…Using this approach the rhesus monoamine oxidase A (MAO-A) expression in the blood of alcohol-naïve subjects was found to be negatively correlated with subsequent alcohol self-administration (Cervera-Juanes et al, 2015). Further, the methylation of the promoter region of the MAO-A gene was associated with MAO-A expression in blood and in the nucleus accumbens (Cervera-Juanes et al, 2016). Because MAO-A is involved in monoaminergic metabolism (serotonin, dopamine and norepinephrine), discrete epigenetic changes altering the expression of this enzyme has direct implications for homeostatic physiological and behavioral processes involved in the risk for heavy drinking.…”
Section: Ii: Assessment Of Risks For Heavy Drinking and Stress Interamentioning
confidence: 99%
“…Importantly, like humans, NHPs show wide individual differences in their chronic intake of alcohol over years, with a large proportion voluntarily drinking amounts similar to human alcoholic chronic drinking levels (Baker et al, 2014; Baker et al, 2017; Mendelson and Mello, 1972;). More broadly, macaques and humans share similar genetic and epigenetic composition (Barr, 2013; Cervera-Juanes et al, 2016). For example, a recent study found CRH and serotonin gene polymorphisms in male rhesus macaques predicted a blunted ACTH response to dexamethasone (Ferguson et al, 2012).…”
Section: I: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be further understood by examining how the epigenome changes across the three components of AUDs: intoxication, withdrawal, and craving (Koob & Volkow, 2010). In this special issue on epigenetics, Cervera-Juanes, Wilhelm, Park, Grant, & Ferguson (this issue) show that within the nucleus accumbens core, which is involved in neurocircuitry for intoxication and withdrawal, chronic low level drinking results in DNA hypomethylation, and high levels of drinking result in hypermethylation. In the prefrontal cortex, which is involved in neurocircuitry for craving, Hashimoto, Gavin, Wiren, Crabbe, and Guizzetti (this issue) show altered gene expression for proteins needed for histone and DNA epigenetic modification creation and maintenance, and they show that ethanol withdrawal has a larger effect on gene expression than ethanol exposure or abstinence.…”
Section: Alcohol-use Disorders – Adulthoodmentioning
confidence: 99%
“…Although there is an emerging literature on the effects of alcohol on epigenetic mediators (Barbier et al, 2015, 2016; Cervera-Juanes, Wilhelm, Park, Grant, and Ferguson, 2016; Pandey, Ugale, Zhang, Tang, and Prakash, 2008; Ponomarev, Wang, Zhang, Harris, and Mayfield, 2012; Warnault, Darcq, Levine, Barak, and Ron, 2013), no study has systematically and comprehensively examined changes in the expression of genes encoding for chromatin modifying proteins after chronic alcohol exposure, alcohol withdrawal, and protracted abstinence.…”
Section: Introductionmentioning
confidence: 99%